2019
DOI: 10.14202/vetworld.2019.700-705
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of conventional polymerase chain reaction and routine blood smear for the detection of Babesia canis, Hepatozoon canis, Ehrlichia canis, and Anaplasma platys in Buriram Province, Thailand

Abstract: Background and Aim: Dog blood parasites are important tick-borne diseases causing morbidity and mortality in dogs worldwide. Four dog blood parasites species are commonly found in Thailand: Babesia canis, Hepatozoon canis, Ehrlichia canis, and Anaplasma platys. They are transmitted easily by tick species. However, there is little prevalence data available in Thailand. Diseases presentation of blood parasites infection is similar, but the treatment of each species is different. Current diagnosis mainly relies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
49
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 29 publications
10
49
5
Order By: Relevance
“…This is especially true in low-socioeconomic countries, that may have little available resources to invest into disease prevention programs [1][2][3]. In particular, countries spanning the tropics must affront an expansive range of CVBDs that comprise a leading cause of fatality in dogs [3][4][5][6]. Bacterial infections can be some of the deadliest CVBDs in such regions with pathogens such as Ehrlichia canis, the causative agent of canine monocytic ehrlichiosis (CME), being the biggest contributor to a raft of life-threatening conditions, including pancytopenia, fever, bleeding tendencies and immunosuppression [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially true in low-socioeconomic countries, that may have little available resources to invest into disease prevention programs [1][2][3]. In particular, countries spanning the tropics must affront an expansive range of CVBDs that comprise a leading cause of fatality in dogs [3][4][5][6]. Bacterial infections can be some of the deadliest CVBDs in such regions with pathogens such as Ehrlichia canis, the causative agent of canine monocytic ehrlichiosis (CME), being the biggest contributor to a raft of life-threatening conditions, including pancytopenia, fever, bleeding tendencies and immunosuppression [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…16S rRNA metabarcoding is better able to elucidate diversity in explorative research by not relying on likely pathogen prevalence in a region nor on a priori knowledge of a pathogen's target genetic sequences, whilst also being better able to characterise coinfection [18,20]. Previous work has already developed a novel 16S and 18S rRNA metabarcoding methodology to characterise the range of blood-borne bacterial, apicomplexan and kinetoplastid organisms infecting canine hosts in Thailand, a country of substantial CVBD diversity [4,8,[21][22][23]. The current research takes this further, by tackling some of the inherent challenges of NGS microbiome research whilst also improving methods to be better at unearthing pathogen diversity in the context of the canine blood micro-environment [24].…”
Section: Introductionmentioning
confidence: 99%
“…The bacterial agglomerates form morulae within the host’s monocytes after being transmitted through a tick bite [ 1 ]. Ehrlichia canis is a common species reported in Thailand [ 6 , 11 - 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Serological tests also are used frequently, but cross-reactions have been reported while the current infection status cannot be determined [ 14 - 16 ]. Polymerase chain reaction (PCR) assays have been developed to diagnose blood parasites, and they yielded high sensitivity and specificity [ 6 , 11 , 13 , 17 ]. Nonetheless, molecular testing necessitates special equipment and is relatively expensive when compared to microscopic or serological methods.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we identified the infection with Anaplasma by PCR and blood smear, but not by the antibody detection because A. platys-like strain isolate is not available. Based on the previous comparison on diagnosis methods, PCR was highly sensitive and endorsed for blood parasite diagnosis (Rucksaken et al 2019, Wardrop et al 2016). In addition, for PCR detection, it is worth noting that only targeting the 16S rRNA gene is not sufficient for the identification of Anaplasma.…”
Section: Discussionmentioning
confidence: 99%